META-ANALISIS KEEFEKTIFAN MODEL PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA SD - Rifai, Moh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
The purpose ofthis research to analize the effectiveness of Student Team Achievement Division (STAD) model in improving social studies learning of elementary scool students. This model is one of cooperative learning that can give student learning motivation. First, the researcher formulated the problem and than collect exiting research data that was already throughgoogle scholar. The research data found of 12 articles and 1 relevantthesis result. The researcher analyzed the result of the study using quantitative comparison methods. Based on the result of the analysis, Student Team Achievement Division (STAD) models are effectively used in improving social studies learning of elementary school students. Increase in students learning of elementary starting from the lowest 6.9 % to the highest 56.6 % with an average increase of 34.61 %.